The body mapping of musculoskeletal complaints for surfers - Putu Sri Putri Laksmi; Wibawa, Ari; M. Widnyana; Kinandana, Gede Parta; Vittala, Govinda (Physical Therapy Journal of Indonesia, 2024)
Background: Surfing is an extreme water sport that consists of various movements, including paddling, popping-up, and wave riding, and has a risk of musculoskeletal complaints. This study aimed to determine the description of musculoskeletal complaints in surfers. Methods: The study used a descriptive observational design with a cross-sectional approach. This study was conducted from February to May 2023 at the halfway club in Kuta Beach, Sanur Beach, and Canggu Beach using the total sampling technique with a total available population of 60 surfers. We included the sample with inclusion criteria and excluded the sample with exclusion criteria. Fifty-one surfers were eligible for the study. Data collection was carried out by interviews using the Nordic Body Map questionnaire. Results: Based on the Nordic Body Map questionnaire, musculoskeletal complaints in surfing players in Bali were a score of 2 (somewhat painful); most of them experienced complaints in the right knee (45.10%) and upper neck (39.22%). The risk level for musculoskeletal complaints in surfers in Bali was 46 people (90.2%) with a low-risk level and five people (9.8%) with a moderate risk level. Conclusion: The most musculoskeletal complaints in surfers in Bali are in the right knee, upper neck, right shoulder, left shoulder, waist, and ankle areas. The risk level for musculoskeletal complaints among surfers in Bali was mainly low, and some had a moderate risk level.